Beyond Plant Microbiome Composition: Exploiting Microbial Functions and Plant Traits via Integrated Approaches - Song, Chunxu; Zhu, Feng; Carrión, Víctor J.; Cordovez, Viviane (Frontiers in Bioengineering and Biotechnology, 2020)
Plants recruit specific microorganisms to live inside and out their roots that provide essential functions for plant growth and health. The study of the microbial communities living in close association with plants helps understanding the mechanisms involved in these beneficial interactions. Currently, most of the research in this field has been focusing on the description of the taxonomic composition of the microbiome. Therefore, a focus on the plant-associated microbiome functions is pivotal for the development of novel agricultural practices which, in turn, will increase plant benefits. Recent advances in microbiome research using model plant species started to shed light on the functions of specific microorganisms and the underlying mechanisms of plant-microbial interaction. Here, we review (i) microbiome-mediated functions associated with plant growth and protection, (ii) insights from native and agricultural habitats that can be used to improve soil health and crop productivity, (iii) current -omics and new approaches for studying the plant microbiome, and (iv) challenges and future perspectives for exploiting the plant microbiome for beneficial outcomes. We posit that integrated approaches will help translating fundamental knowledge into agricultural practices.